DEPENDENCE BETWEEN OF THE CHILD`S DIGESTIVE SYSTEM AND OF FAMILY RELATIONSHIPS - Zimovina, Tеtiana (PSYCHOLOGICAL JOURNAL, 2019)
The article reveals the issue of psychosomatic aspect of the incidence of children’s gastrointestinal tract. One of the main factors at the stage of personality development, influencing personal growth and psychological well-being, is the family. Research results of the dependence between frequency of children’s gastrointestinal tract diseases and features of the relationships between parents and the style of parenting in the family are presented in the article. The study was conducted among families with children of preschool and junior school age, different in status (full and incomplete families). Discovered correlations between children’s diseases of the gastrointestinal system and upbringing features of family can be united in one whole by general theme. This is the excessive demands. In families with children under 6 years of age, there are requirements for parents, too high standards, which mom and dad should to be. In the families bringing up children of elementary school age these requirements are extended for children. Psychosomatic problems arise when the child fails to satisfy his/her needs. In this case a permanent "negative" emotional arousal is formed. It is reflected in bodily sensations, and, sometimes, in the pathological process. The fear of punishment and the impossibility of self-expression are the factors that trigger this "negative" emotional arousal. According to the results of research and analysis of literature, we can conclude that the psychological causes of the children’s disease lie primarily on the parents’ responsibility. Childhood illnesses reflect the parents’ psychological problems. The important factor of both somatic and psychological health are the atmosphere of respect, the acceptance of another person, the ability to recognize own shortcomings, the encouragement of the independence of children, emotional support for their achievements, under the condition of the child's freedom of action.